ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN INVESTASI PADA PERUSAHAAN PERTAMBANGAN LOGAM DAN MINERAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Eko Deswin Miechaels Siringo-Ringo; Sumaizar Sumaizar (Politeknik Bisnis Indonesia, 2020)
Abstract: For companies engaged in providing services, operational costs are a very influential element for the formation of corporate profits. Similarly, the UD. Saroha Serbelawan, so that the management and use of operational costs in this company are always monitored from period to period with a continuous monitoring system to maintain the creation of efficiency and effectiveness of work and to see the responsibility of each part in the deviation that occurs in the use of operational costs. After conducting a review and research on UD. Saroha Serbelawan, it can be seen that in the period of 2004 the company experienced a problem, namely the realization of operating costs in 2004 deviated from a sufficient amount of material from the company's operating budget.